The Influence of Artificial Intelligence on Quality, Understanding, Creativity, and Problem-Solving Ability in Completing College Assignments - Yuhani, Yuhani; Sadiah, Baiti; Safitri, Ulfah; Madya, Siti Nurul; sudarmono, sudarmono (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study discusses the influence of Artificial Intelligence (AI) on students' quality, understanding, creativity, and problem-solving skills in completing their academic assignments. The research employs a qualitative method with structured interviews involving one lecturer and two students as informants. The findings reveal that AI has the potential to enhance student's ability to formulate ideas and improve work efficiency. However, dependency on AI can hinder the development of essential skills such as critical thinking, discipline, and reading. Therefore, AI must be used wisely to support independent and active learning processes.